Development of Korean Medicine Clinical Pathways for Hip and Hand Degenerative Arthritis - Seon Changwoo; Kim Min-jeong (Journal of Acupuncture Research)
Background: This study aimed to develop standard clinical pathways (CP) for patients with degenerative hip and hand arthritis, ensuring consistent care, maximizing treatment effectiveness, and enhancing clinical applicability in Korean medicine. Methods: The CPs were developed based on the 2024 Korean Medicine Clinical Practice Guidelines, refined through a literature review and expert consultations, and validated using a 10-point Likert scale survey among 11 experts in Korean medicine, covering topics such as patient assessment, diagnostic tests, treatment methods, and patient education. Results: Most items demonstrated high validity with median values > 8. However, Korean medicine tests and laser acupuncture had lower scores, indicating lower perceived relevance. Conclusion: The developed CPs provide a framework for clinical application, requiring future evaluations and refinement to enhance patient care and standardize Korean medicine treatments for degenerative arthritis.